Clot composition and treatment approach to acute ischemic stroke: The road so far - Singh, Paramdeep (Medknow Publications & Media Pvt Ltd, 2013)
Recent histological studies of thrombi retrieved from patients with an acute ischemic stroke using the endovascular thrombectomy devices and correlation with early vessel computed tomography (CT) and magnetic resonance imaging (MRI) characteristics have given relevant insights into the pathophysiology of thrombotic lesions and may facilitate the development of improved reperfusion treatment approaches. We present a review of recent studies on the histopathologic analysis of thrombi, studies of MRI, and CT imaging correlation with thrombus histology, and detailed structural analysis of thromboemboli retrieved by thrombectomy devices during an acute ischemic stroke.